SIMULATION OF GROUNDWATER CONTAMINATION BY LEAKAGE FROM WASTE-FILLED MINE - Mojtaba Dehqani Tafti (Faculty of Mining, Geology and Petroleum Engineering, 2021)
Mining wastes are a great source of pollutants. Open-pit backfill materials can be found as waste rock and as tailings. The aim of the current study was the investigation of the contaminant transportation pathways by groundwater flow from these waste materials through heterogeneous porous media. Numerical Lattice Boltzmann Method (LBM) was used for examining the effects of different factors on pollutant transportation through groundwater beneath the waste materials. Grain size, vertical and horizontal fracturing, and hydraulic pressure gradient were factors considered here. The results showed that contaminant transportation by the groundwater flow from the waste materials through porous media depends on primary and secondary matrix porosity of the open-pit material, heterogeneity in permeability of aquifer rock, and hydraulic head of groundwater.